The art of the organiser: Raphael Samuel and the origins of the History Workshop. Issue 3 (3rd May 2016) - Scott-Brown, Sophie
Abstract : The History Workshop movement took its stance on the democratisation of history making, becoming notorious for its exuberant gatherings and impassioned 'histories from below'. At the centre of the early Workshop was the British historian Raphael Samuel, who has been described as the personification of its intellectual and ethical politics. This paper examines Samuel's role in the Workshop arguing that his distinctive intellectual personality was critical in shaping its early form and ethos. Drawing on a biographical approach, it explores the development of this persona over the course of his formative years. It argues that Samuel's life history provides an insight into the renewed appeal of libertarian ideas in post-war British radical political and educational thought and that as an individual he illuminates the application of these ideas to the social role of the historian-educator.